Tussenruimte. - Anthoons, Jan; Van Eetvelt, Vic; Vanfleteren, Hilde; Provinciaal Tredcentrum Baljuwhuis, Galmaarden; Biënnale Galmaarden 1998 (Galmaarden : Provinciaal Trefcentrum Baljuwhuis, 1998)
Aguirre y Otegui, Philip ; Jambers, Mark ; 't Jolle, Sven ; Lauwaert, Beatrijs ; Lohaus, Bernd ; Meyers, Koen ; Boelens, Peter ; Vandevelde, Ludwig ; van Soom, Luk ; Voet, Heidi ; et al.
Tussenruimte, Provinciaal Trefcentrum Baljuwhuis, Galmaarden, 1998
kunstcatalogus